2022
DOI: 10.1200/jco.2022.40.16_suppl.9570
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter real-world data of adjuvant treatment and disease outcome of patients with melanoma with high-risk of recurrence.

Abstract: 9570 Background: Clinical trials demonstrated a significantly improved recurrence-free survival (RFS) of melanoma patients treated adjuvantly with immune checkpoint inhibition (ICI) and targeted therapy (TT). As data from controlled trials are based on selected populations, we investigated melanoma patients with high risk of recurrence who opted for ICI, TT, or no adjuvant treatment (NoTx) under real-world conditions. Methods: In a prior analysis of this multicenter, retrospective cohort study, patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
6
3
0
Order By: Relevance
“…The RFS and OS rates reported for BRAF/MEK-treated patients in this study are similar to the RFS and OS rates reported in the registration trials [15,37,38]. Livingstone et al described a recurrence rate of 35% in TT and 48% in ICI at a median follow-up time of 25.3 and 24.6 months, respectively, in resected stage III/IV melanoma patients registered into a central German registry [40]. Unfortunately, our data are based on shorter follow-up times, as BRAF/MEK-inhibition therapy was approved and reimbursed later in the Netherlands compared to Germany.…”
Section: Braf/mek-inhibition Therapy Toxicity Premature Treatment Ces...supporting
confidence: 87%
See 1 more Smart Citation
“…The RFS and OS rates reported for BRAF/MEK-treated patients in this study are similar to the RFS and OS rates reported in the registration trials [15,37,38]. Livingstone et al described a recurrence rate of 35% in TT and 48% in ICI at a median follow-up time of 25.3 and 24.6 months, respectively, in resected stage III/IV melanoma patients registered into a central German registry [40]. Unfortunately, our data are based on shorter follow-up times, as BRAF/MEK-inhibition therapy was approved and reimbursed later in the Netherlands compared to Germany.…”
Section: Braf/mek-inhibition Therapy Toxicity Premature Treatment Ces...supporting
confidence: 87%
“…A recent follow-up study to the Lodde et al study by Livingstone et al reported similar real-world results to our present study. In their study, the authors showed slightly higher premature discontinuation rates (44%) in real-world patients treated with TT and showed that 60% of patients who prematurely discontinued treatment had done so due to toxicity [40]. The discrepancy in grade ≥3 adverse events rates and treatment discontinuation rates due to any grade adverse events might be due to the under-reporting of these events in daily clinical practice.…”
Section: Braf/mek-inhibition Therapy Toxicity Premature Treatment Ces...mentioning
confidence: 92%
“…Recently in ASCO Annual meeting, a multicenter real-world data of adjuvant treatment from German with 288 Stage III BRAF-mutant melanoma patients identified, also showed that risk of recurrence was higher and earlier for immunotherapy than for targeted therapy. 15 In their report, 1-year and 2-year RFS for adjuvant D + T was 88% and 66%, which was similar to the data from COMBI-AD. But for anti-PD1 immunotherapy, 2-year RFS declined to only 45%, which was much worse than 68% reported in KEYNOTE 054.…”
Section: Discussionsupporting
confidence: 69%
“…Our study suggested that in real‐world experience, for Chinese melanoma, adjuvant immunotherapy did not show a comparable benefit to adjuvant dual‐targeted therapy, which was similar to some other studies. Recently in ASCO Annual meeting, a multicenter real‐world data of adjuvant treatment from German with 288 Stage III BRAF‐mutant melanoma patients identified, also showed that risk of recurrence was higher and earlier for immunotherapy than for targeted therapy 15 . In their report, 1‐year and 2‐year RFS for adjuvant D + T was 88% and 66%, which was similar to the data from COMBI‐AD.…”
Section: Discussionsupporting
confidence: 59%
“… 23 In line, a recent subgroup analysis by Lodde et al and a propensity matched analysis by Wouters et al reported that adjuvant DT showed superior RFS outcomes in a real-world cohort of resected melanoma patients when compared with adjuvant anti-PD1 therapy. 24 25 …”
Section: Discussionmentioning
confidence: 99%